PENGARUH BRAND COMMUNICATION, BRAND IMAGE, BRAND SATISFACTION, BRAND TRUST TERHADAP BRAND LOYALTY TEH PUCUK HARUM DI SURABAYA - Annisa Dieni Eka P.; Dudi Anandya; Indarini Indarini (Perpustakaan Universitas Surabaya, 2018)
The purpose of the study was to analyze and determine the influence of brand communication, brand image, brand satisfaction, brand trust would effect brand loyalty Teh Pucuk Harum in Surabaya. This study uses 170 respondents residing in Surabaya, minimum highschool education or equal, buying and consuming the product of teh pucuk harum, have seen the promotional activities of teh pucuk harum and know the difference between teh pucuk harum with other ready to drink tea.This research using Structural Equation Modelling (SEM) approach with Lisrel 8.7 for Windows. Sampling technique used in this research are non probability sampling with this type of purposive sampling. The data were collected directly from respondents who meet the characteristics of the population by spreading questionnaires.The results of this study showed found that brand communication, brand image, brand satisfaction and brand trust have a positive and significant influence toward brand loyalty teh pucuk harum in surabaya.